(untitled) (Proceedings of Southern Federal University. Philology, 2026)
10.18522/1995-0640-2026-1-34-46 The role of the comedian and tragedian in Chekhov’s vaudevilles is analyzed in comparison with their counterparts in Shcheglov’s plays. The internal connection between these roles and the role of inversion in the process of their mutual reversibility are shown (a comedian by nature and a tragedian against his will). It proves that the characters of vaudeville heroes have a matrix character, that is, they are presented by the authors as ready-made and well-known. Chekhov’s vaudevilles are built on the basis of taking into account the role, in line with the tradition that Shcheglov’s vaudevilles represented. Chekhov’s plays, written for the Art Theatre, were built on overcoming the principle of role. The protagonists of these plays transcend a specific type of role. The roles of comedian and tragedian were retained in an inverted version by minor characters in Chekhov’s major plays. Key words: role, comedian, tragedian, vaudeville, A. P. Chekhov, I. L. Shcheglov